Academic cultural barriers in the implementation of project-based curriculum in private Islamic universities - Khalimatus Sadiyah; Mahalli Mahalli; Ma'as Shobirin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study explores cultural and structural barriers to implementing project-based curricula in private Islamic universities through a qualitative case study at Wahid Hasyim University (Semarang) and Nahdlatul Ulama Islamic University (Jepara). Data were collected from 18 key informants’ university leaders, programmed heads, and lecturers using in-depth interviews, classroom observations, and curriculum document analysis. Conservative academic culture is reflected in lecturer-centred teaching, rigid curriculum interpretation, limited interdisciplinary collaboration, and restricted student autonomy. Findings reveal uneven adoption of project-based curricula across programmed, continued dominance of lecturer-centered practices shaped by leadership commitment and institutional policies, and limited readiness of lecturers and students for collaborative learning. Structural constraints, including assessment systems and workload regulations, further impede innovation and student participation. The study concludes that curriculum reform must be accompanied by transformation in academic culture and governance. It recommends capacity-building initiatives, policy alignment, and participatory academic practices to ensure sustainable implementation of project-based curricula in private Islamic higher education institutions.